APPLICATION OF KETOROLAK IN THE PREHOSPITAL TREATMENT OF RENAL COLIC - CASE REPORT AND LITERATURE REVIEW - Janković, Tamara; Đorđević, Stefan; Vukićević, Verica (Halo 194 Scientific Journal of Emergency Medicine, 2025)
Introduction:Renal colic (RC) is a sudden onset of severe pain in the costovertebral angle on the corresponding side.The clinical presentation is usually sudden,unilateral pain in  the lumbar region,followed by nausea/vomiting and dysuric complaints.Objective:Presentation of a patient with sudden onset of RC.Case report:A 28-year-old patient stated that she felt a strong,sudden pain in the lumbar region on the left side,with propagation in the groin,nausea and sweating.The renal lobes are painfully sensitive to succussion,more intensely on the left.The patient was transported to the hospital.During transportation,ketorolac 30mg and hyoscine-butylbromide 20mg were administred intravenously.By the time she arrived at the hospital,the pain had stopped.Conclusion:Ketorolac is a very effective analgesic in the treatment of RCit has a stronger analgesic effect than opioids.In the prehospital treatment of RC,when choosing drugs and their dosage,the therapy should be adjusted individually for each patient.
Keywords: renal colic, urolithiasis, ketorolac, ibuprofen, opioids